Mothers’ Knowledge and Noncompliance of Childhood Vaccination in Primary Health Care Centers at Mosul City - Hana A. Alsaeed; Rayyan Ibrahim Khaleel; Hanaa Hussein Mukhlif (Medical Journal of Babylon)
Background: A vaccine ensures children that they are immune to or resistant to an infectious disease. Objectives: The study aimed to assess mothers’ knowledge. In addition, identify the reasons for noncompliance with vaccination of their children, and the relationship between the mothers’ knowledge with their educational level. Materials and Methods: A descriptive study was designed for a sample of 250 mothers attending primary health care centers between September 15, 2022, and December 20, 2022, for their children’s immunizations. The tool of the study contains questions about the sample’s sociodemographic characteristics. As well as 7 questions about the mother’s knowledge and 12 questions about reasons for children’s inadequate immunizations. Descriptive and inferential statistics were performed. Results: The results revealed that regarding mothers’ knowledge about immunization, the study revealed that most mothers do not have sufficient knowledge about vaccinations for their children. Most of them believe that vaccines can be harmful to the child (81.2%). The study found a linkage between mothers’ knowledge of vaccinations with their educational level. Conclusion: This study concludes that insufficient knowledge of mothers about vaccination and the reasons for fear of side effects and the unavailability of the vaccine entails effective dissemination of information, campaigning, and family involvement.